What is Rate-Limiting during Sustained Synaptic Activity: Vesicle Supply or the Availability of Release Sites - Neher, Erwin (Frontiers in Synaptic Neuroscience, 2010)
For some types of synapses the availability of release-ready vesicles is a limiting factor during ongoing activity. Synaptic strength in this case is determined both by the recruitment of such vesicles and the probability of their release during an action potential. Here it is argued that not the availability of vesicles is the limiting factor for recruitment, but rather the availability of specific sites to which vesicles can dock.